Assistance of School Principals in Building Student Character at Madrasah Ibtidaiyah Ummul Qur'an An-Nurani - Suriyah, Suriyah; Kalsum, Umi; Juliana, Risna; Marsela , Medes; Kamilah, Nurul (CV. Pustaka An Nur, 2024)
The purpose of this research is to determine the assistance of teachers and school principals in student character education. Community service activities through the assistance of the head of Madrasah Ibtidaiyah Ummul Qur'an An-Nurani Tembilahan can be carried out well according to plan. From the results of this mentoring activity, it can be concluded that the impact of this activity was a positive response from the principal, teachers, employees and students of Madrasah Ibtidaiyah Ummul Qur'an An-Nurani Tembilahan. The students' character also improved because there were activities that provided students with additional knowledge about improving the character formation of students at Madrasah Ibtidaiyah Ummul Qur'an An-Nurani Tembilahan which was carried out well. Then, by creating a conducive madrasah atmosphere, students can feel at home in carrying out learning. For future improvements, there are several recommendations, namely that optimization of this program needs to be carried out to obtain maximum results, and the implementation of updated library management must continue.Keywords: Mentoring, Principal, Student Character.